Keterlibatan Evrazisky Soyuz Molodezhi dalam Konflik di Ukraina - Firdaus, Yoga Arfiansyah; Rosyidin, Mohamad; Hanura, Marten (Journal of International Relations, 2021)
Evrazisky Soyuz Molodezhi (ESM) is one of the international organizations actively involved in the Ukrainian conflict. This involvement includes the use of network warfare tactics (stevaia voina), guerrilla warfare (partizanskiye deystviya), forming an anti-US international alliance (‘Coalition of Disatisfied’), and aggressive forms of action. This study aims to explain the motives for ESM involvement in the Ukrainian conflict. This study used a qualitative research method with an explanative research type through the mechanism of idea as road maps approach by Goldstein & Keohane. This study concludes that ESM's involvement in the Ukrainian conflict is influenced by ideas such as the dualism of ‘The Great War of the Continents’, Asimmetrichnaya Voyna, the ‘Coalition of Disatisfied’, and the significance of Novorossiya embedded in Neo-Eurasianism ideology. These ideas influence ESM preferences and the pathways to achieve them.